Morfología de los estados preimaginales de Gonatopus bonaerensis, y consideraciones sobre la morfología interna de sus larvas inmaduras (Hymenoptera, Dryinidae) - Mangione, Susana (2004)
The postembryonic stages of Gonatopus bonaerensis Virla (Dryinidae), parasitoid of planthoppers (Delphacidae) vectors of plant diseases in Argentina, are described. The external morphology pattern of the eggs and larval stages does not differ from other species of Gonatopodinae already known. The chaetotaxy of the head is described and compared with other well-known species. The studies on the internal anatomy put emphasis in the description of the tegument, cephalic lobes and alimentary canal. The morphology of the muscular pharynx and the sphincter between esophagus and gastric cavity of G. bonaerensis larvae (formerly located in the genus Dicondylus) differs thoroughly with that described for G. chilensis (Olmi) (formerly belonging to the genus Pseudogonatopus). These divergences allow us to infer that, mechanically, the form of feeding of both species is different, being passive in G. bonaerensis and active in G. chilensis; these differences impose the necessity to study other species to clarify the taxonomic position of both groups.